Pain Perception Can Be Modulated by Mindfulness Training: A Resting-State fMRI Study - Su, I-Wen; Wu, Fang-Wei; Liang, Keng-Chen; Cheng, Kai-Yuan; Hsieh, Sung-Tsang; Sun, Wei-Zen; Chou, Tai-Li (Frontiers in Human Neuroscience, 2016)
The multi-dimensional nature of pain renders difficult a holistic understanding of it. The conceptual framework of pain is said to be cognitive-evaluative, in addition to being sensory-discriminative and affective-motivational. To compare participants’ brain-behavior response before and after a six-week mindfulness-based stress reduction (MBSR) training course on mindfulness in relation to pain modulation, three questionnaires (the Dallas Pain Questionnaire, Short Form McGill Pain Questionnaire-SFMPQ, and Kentucky Inventory of Mindfulness) as well as resting-state functional magnetic resonance imaging (fMRI) were administered to participants, divided into a pain-afflicted group (N=18) and a control group (N=16). Our results showed that the pain-afflicted group experienced significantly less pain after the mindfulness treatment than before, as measured by the SFMPQ. In conjunction, an increased connection from the anterior insular cortex (AIC) to the dorsal anterior midcingulate cortex (daMCC) was observed in the post-training pain-afflicted group and a significant correlation was found between AIC-daMCC connectivity and SFMPQ scores. The results suggest that mindfulness training can modulate the brain network dynamics underlying the subjective experience of pain.